Dog Man. Twenty thousand fleas under the sea - Pilkey, Dav, 1966-; Garibaldi, Jose; Dzioba, Wes; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (New York : Graphix, an imprint of Scholastic, 2023)
Piggy is back, and his newest plot is his most diabolical yet. Dog Man and the rest of your favorite characters must join together. What new villains are on the horizon? Where are they all comign from. And who will step forward to save the city when scoundrels sabotage our Supa Buddies?
Keywords: Dogs -- Comic books, strips, etc; Police -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Cartoons and comics; Action and adventure comics; Humorous comics; Graphic novels; Comics (Graphic works)